Simultaneous bi-station measurements of mesospheric waves from Indian low latitudes - Taori, Alok; Parihar, Navin (My University, 2011)
Coordinated mesospheric night-airglow measurements have been carried out from two stations, Gadanki (13.5 N, 79.2 E) and Allahabad (25.5 N, 81.9 E), India during April 2009 to study the common gravity wave features. With two nights of coordinated measurements we find some of the wave periodicities to be similar at the two locations. Simultaneous OH and O2 intensity measurements over Gadanki reveal these features to be upward propagating gravity waves while the coordinated OH intensity measurements of similar waves from Allahabad show the large spatial extent of these waves.
Keywords: Mesosphere; Gravity wave; Propagation; Dissipation; Mesospheric waves; Low latitudes; Night-airglow; Gadanki; Allahabad; All-sky imager; Mesosphere Lower Thermosphere Photometer